THE ROLE OF LOCAL WISDOM IN EDUCATION BRANDING: FRAMING AS A STRATEGY TO STRENGTHEN THE COMPETITIVE ADVANTAGE OF EDUCATIONAL INSTITUTIONS - Anwar, Shodiqul; Alfaridli, Muhammad Alfi; Bakron S, Muhammad; Abdullah, Abdullah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Abstract:This study aims to explore the strategy of local wisdom-based branding to enhance the competitive advantage of SMA Islam Miftahul Arifin. Branding rooted in local cultural values is expected to strengthen the identity of this educational institution and increase its appeal in the eyes of the community, especially in the face of increasingly fierce competition in the education sector. The research was conducted at SMA Islam Miftahul Arifin, located in Patokan Village, Bantaran Subdistrict, Probolinggo Regency. This location was chosen because of its community's strong adherence to local cultural values, which play a crucial role in the branding strategy implemented by the institution. The research method used is qualitative descriptive with a case study approach. Data were collected through observations, in-depth interviews with the principal, teachers, staff, and parents, as well as document analysis related to the branding strategies that have been applied at the school. The data analysis technique employed was thematic analysis, which allows the researcher to identify and analyze significant patterns in the data collected. The aim of this study is to provide an in-depth understanding of how a local wisdom-based competitive advantage framing strategy can be implemented in educational institution branding, and how this strategy affects the image and quality of education at SMA Islam Miftahul Arifin. This study is expected to contribute to the development of effective branding strategies for other educational institutions that aim to strengthen their position amid intense competition in the educational sector. By leveraging local wisdom in their branding, schools can build a distinctive identity that resonates with the values of the surrounding community, ultimately helping them to attract more students and stakeholders. In conclusion, the findings from this research highlight the importance of local wisdom in educational branding as a means of enhancing competitive advantage. By integrating local culture into their branding strategies, educational institutions can not only improve their appeal but also ensure that their values and mission align with the needs and expectations of the community they serve.